Interactive Multimedia Lectora Inspire Based on Problem Based Learning: Development in The Optical Equipment. (February 2019) - Irwandani; Umarella, S; Rahmawati, A; Meriyati; Susilowati, N E
Abstract: The integration of technology in the learning process is needed in this era where technology as the part of media can enhance the understanding and attention of students. This study aims to develop interactive multimedia Lectora Inspire based on Problem Based Learning model in the material of optical equipment. Research and development are following a step development of Borg & Gall. Based on the results validation of the product, the feasibility of the product from the material experts is 86%, from media experts is 93%, and from teachers is 87%. The products were then tested on a small scale and attractiveness of the percentage obtained by 83%. Furthermore, in field trials, the percentage of attractiveness obtained is 80%. Based on these results, interactive multimedia Lectora Inspire based on Problem Based Learning model in the material of optical equipment for eleventh class can be used as a learning media.